THE PLACE OF THE EDUCATIONAL ACTIVITY OF THE TURKISTAN JADIDS IN THE PROCESS OF NATIONAL DEVELOPMENT OF UZBEKISTAN - Turayeva Marjona Said qizi (Western European Studies, 2025)
This article discusses the educational activities of the Jadids of Turkestan and the role of these movements in the national development of Uzbekistan, as well as the role of the Jadids in increasing literacy in the rise of the people, the ideas of science and freedom are revealed in their works and through new methods of schools. It talks about the true devotees who even sacrificed their lives to show how necessary science is in awakening the nation
Keywords: Jadid; enlightenment; Usuli Jadid; Usuli schools